Microbial Metabolites: The Emerging Hotspot of Antiviral Compounds as Potential Candidates to Avert Viral Pandemic Alike COVID-19 - Raihan, Topu; Rabbee, Muhammad Fazle; Roy, Puja; Choudhury, Swapnila; Baek, Kwang-Hyun; Azad, Abul Kalam (Frontiers in Molecular Biosciences, 2021)
The present global COVID-19 pandemic caused by the noble pleomorphic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has created a vulnerable situation in the global healthcare and economy. In this pandemic situation, researchers all around the world are trying their level best to find suitable therapeutics from various sources to combat against the SARS-CoV-2. To date, numerous bioactive compounds from different sources have been tested to control many viral diseases. However, microbial metabolites are advantageous for drug development over metabolites from other sources. We herein retrieved and reviewed literatures from PubMed, Scopus and Google relevant to antiviral microbial metabolites by searching with the keywords ‘antiviral microbial metabolites’, ‘microbial metabolite against virus’, ‘microorganism with antiviral activity’, ‘antiviral medicine from microbial metabolite’, ‘antiviral bacterial metabolites’, ‘antiviral fungal metabolites’, ‘antiviral metabolites from microscopic algae’ and so on. For the same purpose, the keywords ‘microbial metabolites against COVID-19 and SARS-CoV-2’ and ‘plant metabolites against COVID-19 and SARS-CoV-2’ were used. Only the full text literatures available in English and pertinent to the topic have been included and those which are not available as full text in English and pertinent to antiviral or anti-SARS-CoV-2 activity were excluded. In this review, we have accumulated microbial metabolites that can be used as antiviral agents against a broad range of viruses including SARS-CoV-2. Based on this concept, we have included 330 antiviral microbial metabolites so far available to date in the data bases and were previously isolated from fungi, bacteria and microalgae. The microbial source, chemical nature, targeted viruses, mechanism of actions and IC50/EC50 values of these metabolites are discussed although mechanisms of actions of many of them are not yet elucidated. Among these antiviral microbial metabolites, some compounds might be very potential against many other viruses including coronaviruses. However, these potential microbial metabolites need further research to be developed as effective antiviral drugs. This paper may provide the scientific community with the possible secret of microbial metabolites that could be an effective source of novel antiviral drugs to fight against many viruses including SARS-CoV-2 as well as the future viral pandemics.